1995
DOI: 10.1095/biolreprod53.6.1365
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Normal Adult Penile Erectile Response in Aged Rats by Long-Term Treatment with Androgens1

Abstract: In order to determine whether the aging-related impairment of penile erection can be corrected by exogenous androgens, 20-mo-old ("old") rats received implants of Silastic tubing containing either testosterone (T) or dihydrotestosterone (DHT). Untreated aged-matched rats were used as reference controls, and values were compared with those obtained previously for 5-mo old ("adult") rats. After 45 days, groups of six rats were submitted to electrical field stimulation of the cavernosal nerve (EFS), and the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 48 publications
2
58
0
4
Order By: Relevance
“…There is evidence for involvement of the NO/cGMP system. Thus, Garban et al (1995) found that the soluble NOS activity decreased significantly in penile tissue from senescent rats. Lower NOS mRNA expression was found in old rats than in young rats (Dahiya et al, 1997).…”
Section: A Risk Factors and Conditions Associated With Erectile Dysfmentioning
confidence: 93%
“…There is evidence for involvement of the NO/cGMP system. Thus, Garban et al (1995) found that the soluble NOS activity decreased significantly in penile tissue from senescent rats. Lower NOS mRNA expression was found in old rats than in young rats (Dahiya et al, 1997).…”
Section: A Risk Factors and Conditions Associated With Erectile Dysfmentioning
confidence: 93%
“…29 In adult rats, the decrease in NOS activity that followed castration is restored with androgen replacement, whereas no additional NOS activity is observed when intact animals were given additional androgens. 30 In dogs, castration leads to a decline in the ratio of intracavernosal pressure to peak systolic pressure and there is also evidence of higher outflow rates in the castrate animals. 31 A decline in the magnitude of the induced intracavernosal pressure rise during erection is observed but the investigators attributed the lower intracavernosal pressure to be accompanying reduction in mean arterial pressure.…”
Section: Role Of Ischemic Factorsmentioning
confidence: 99%
“…Clinical and animal studies provided evidence that androgens protect cavernous SM, promoting cell proliferation and maintaining functional integrity (Andersson and Wagner 1995;Aversa et al 2000Aversa et al , 2003Garban et al 1995;Huang et al 2008;Lue and Dahiya 1997;Mills et al 1992;Shabsigh 1997). It was also demonstrated that androgen deficiency contributes to endothelial damage in a castrated rat model (Lu et al 2007).…”
mentioning
confidence: 98%